Seminar on Finances for Industrial Development of U.P. During the Fourth Plan - Planning Commission (Planning Commission, 1964)
I am extremely happy to extend to you all a most cordial, welcome to this Seminar on "Finances for the Industrial Development of U.P. during the Fourth Plan". do not wish to usurp the privilege of the Vice-Chancellor to welcome you to this University. I have merely risen to give you a background of this Seminar. Planning has come to occupy a very important place in our country and it is essential that the Universities, the governments and other agencies concerned with the formulation of plans and those that are responsible for implementing them, viz. government departments, public and private enterprises, financial institutions, etc. should all work together to prepare the best possible plan.
Department of Commerce